Ant-gardens on the giant bamboo gigantochloa scortechinii(Poaceae) in West-Malaysia - Hashim, Rosli; Kaufmann, E.; Weissflog, A.; Maschwitz, U. (2001)
We report the first experimental evidence of seed collecting behavior in an ant-garden-inhabiting ant species in the Palaeotropics. Vascular epiphytes growing on the giant bamboo Gigantochloa scortechinii (Poaceae) were collected at Ulu Gombak, West Malaysia. Sixteen epiphyte species were growing in carton-nests of seven ant species. All epiphytes on bamboo were associated with ants. The most frequent ant species (Crematogaster sp. 1, Myrmicinae) apparently nests only on bamboo. It was tested for its behavior towards the seeds of three epiphyte species (Dischidia nummularia (Asclepiadaceae), Aeschynanthus fecundus, Aeschynanthus albidus (Gesneriaceae)) and one non-epiphyte species (Emilia sonchifolia (Asteraceae)). Most of the offered epiphytes' seeds were carried to the nest, while the seeds of the non-epiphyte were ignored or even discarded. There were no species-specific differences among the epiphytes' seeds. We hypothesize that seed-collecting behavior is necessary for the establishment of ant-garden associations and for the colonization of bamboo culms by epiphytes. The smooth-surfaced and relatively short-lived bamboo culms would not host epiphytes without the mediation of the ants. We suspect that ants may also have a great influence on the distribution of epiphytes on other hosts. In this paper we describe ants as active nest builders and seed collectors that give certain epiphytes the opportunity to live in open and sun exposed habitats on bamboo. Benefits to the ants are discussed as well.